Graphene magnetic wave-absorbing material as well as preparation method and application thereof

The preparation of CoFe2O4/RGO composite material by one-step hydrothermal method solves the problems of large density and narrow absorption frequency band of traditional electromagnetic wave absorbing materials, and realizes a low-energy consumption and simple preparation process, which meets the thin, light, wide and thinner of the new electromagnetic wave absorbing materials. Strong requirements and the process is suitable for industrial production.

CN119143123APending Publication Date: 2024-12-17JIANGSU UNIV OF TECH

Patent Information

Application Number
CN202411284283.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorbing materials have problems such as large density, narrow absorption frequency band and weak strength, which cannot meet the requirements of the new electromagnetic wave absorbing materials of 'thin, light, wide and strong'. Moreover, their preparation process conditions are harsh and their energy consumption is high, so they are not suitable for industrialization. Mass production.

Method used

CoFe2O4 and tulle-shaped RGO are compounded by one-step hydrothermal method. CoFe2O4/RGO composite material is prepared by dispersing iron and cobalt sources into the RGO solution, adding sodium acetate and polyethylene glycol, and then cooling after heating reaction. , the 'sandwich' structure formed by nanoparticles loading on the stacked folded RGO and forming irregular pores and channels.

Benefits of technology

It realizes a low-energy consumption, simple and convenient preparation process, high purity of the product, suitable for large-scale production, composite materials have excellent magnetic permeability and magnetic recombination effect in specific frequency bands, reducing magnetic loss, and achieving optimal impedance matching and attenuation. Characteristics meet the requirements of the new electromagnetic wave absorbing materials of 'thin, light, wide and strong'.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143123A_ABST
    Figure CN119143123A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene magnetic wave-absorbing material and a preparation method and application thereof.A one-step hydrothermal method is creatively adopted for compounding a magnetic loss type material (CoFe2O4) and a resistance loss type material (RGO) to prepare a novel efficient wave-absorbing performance material, specifically, an iron source and a cobalt source are dispersed into an RGO solution, then sodium acetate and polyethylene glycol are dissolved in the RGO solution, cooling is conducted after heating reaction, and the graphene magnetic wave-absorbing material is obtained. And separating, washing and drying to obtain the product. According to the graphene magnetic wave-absorbing material, the optimal impedance matching and the excellent attenuation characteristic are achieved through the synergistic effect of the two components, and the excellent electromagnetic wave absorbing performance is shown under various thicknesses or even ultra-thin thicknesses. In addition, the material source is wide, the cost is low, the preparation process is green, simple and feasible, the method is suitable for large-scale production, and a theoretical method and a preparation route are provided for application in the aspect of electromagnetic wave absorption in the national defense and civil fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphene magnetic wave-absorbing material and a preparation method and application thereof, belonging to the technical field of wave-absorbing materials. Background Art

[0002] Traditional electromagnetic wave absorbing materials have disadvantages such as high density, narrow absorption band and weak strength, which cannot meet the requirements of "thin, light, wide and strong" for new electromagnetic wave absorbing materials. Recent studies have shown (Metals, 2023, 13(7):1220; Micro-Nano Electronics Technology, 2024, 61:66-75; Journal of Magnetism and Magnetic Materials, 2023, 588:171447) that the composite of multiple absorbing materials through special structural design is conducive to obtaining electromagnetic wave absorbing materials with excellent comprehensive performance.

[0003] As a new type of two-dimensional carbon material, graphene is highly favored in the field of absorbing materials due to its excellent dielectric properties, mechanical properties, high specific surface area, layered structure and light weight. Chinese patent CN202011030383.9 uses graphene oxide as a carbon source, impregnates nitrates of magnetic metals such as Fe, Co, and Ni, and then calcines it under a protective atmosphere to obtain a magnetic metal or its oxide / graphene composite absorbing material through thermal decomposition and carbon thermal reduction reaction; Chinese patent CN202410003686.3 spray-dries a mixed dispersion containing graphene oxide and magnetic metal to obtain a precursor powder, and then calcines the precursor powder under a nitrogen-hydrogen mixture to prepare an absorbing material.

[0004] Although these graphene-based composite absorbing materials all have certain absorbing functions, their absorbing performance is still relatively poor. In addition, their preparation requires strict control of reaction temperature and gas conditions, harsh process conditions and high energy consumption, which is not conducive to industrial mass production. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing a graphene magnetic absorbing material, which is simple, convenient, low-carbon and environmentally friendly, and is conducive to industrial large-scale application.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a graphene magnetic wave absorbing material comprises dispersing an iron source and a cobalt source into a RGO solution, dissolving sodium acetate and polyethylene glycol, heating for reaction, cooling, and then separating, washing, and drying to obtain a CoFe2O4 / RGO composite material;

[0008] The molar ratio of iron to cobalt in the iron source and the cobalt source is (1-4):1;

[0009] The mass ratio of the iron source, the cobalt source and the RGO in the RGO solution is (53-81):(17.7-46.7):(0.3-1.3);

[0010] The mass ratio of RGO, sodium acetate and polyethylene glycol is (0.007-0.042):(1.8-4.5):(0.2-1.5).

[0011] Preferably, the iron source is FeCl3·6H2O; and the cobalt source is CoCl2·6H2O.

[0012] Preferably, the preparation method of the RGO solution is to disperse graphite oxide powder and sodium dodecylbenzene sulfonate in water and add hydrazine hydrate solution, and then filter and wash after water bath reaction to obtain RGO; and then disperse the RGO in ethylene glycol to obtain the RGO solution.

[0013] Preferably, the conditions for incorporating sodium acetate and polyethylene glycol are as follows: adding sodium acetate and polyethylene glycol to the RGO solution, ultrasonically treating; and stirring at 25-80° C. for 1-5 h before heating for reaction.

[0014] Preferably, the heating reaction conditions are: 120-200° C. for 6-10 h.

[0015] Preferably, the ratio of graphite oxide powder, sodium dodecylbenzene sulfonate and hydrazine hydrate solution is (120-150) mg: (110-150) mg: (0.3-1) mL, and the concentration of hydrazine hydrate solution is 70-85 wt %.

[0016] Preferably, the conditions for the water bath reaction are: 70-90° C., 15-30 h.

[0017] Preferably, the concentration of RGO in the RGO solution is 0.5-1 mg / mL.

[0018] The second object of the present invention is to provide a graphene magnetic absorbing material, which has excellent absorbing performance.

[0019] In order to achieve the above object, the technical solution adopted by the present invention is:

[0020] A graphene magnetic wave absorbing material is prepared by any of the above methods;

[0021] And in the absorbing material, CoFe2O4 nanoparticles are loaded on the RGO with laminated wrinkles and form a sandwich structure containing irregular pores and / or channels;

[0022] Wherein, the particle size of CoFe2O4 nanoparticles is 10-40nm.

[0023] The present invention also provides an application of a graphene magnetic wave absorbing material prepared by any of the above methods in electromagnetic wave absorption.

[0024] The beneficial effects of the present invention are:

[0025] 1. The present invention creatively uses a one-step hydrothermal method to composite spherical CoFe2O4 with gauze-like RGO. The raw material source is wide and the cost is low. It has the advantages of simple reaction process, high efficiency, high product purity and low energy consumption. It is suitable for large-scale production and provides a theoretical method and preparation route for the application of electromagnetic wave absorption in the defense and civilian fields.

[0026] 2. In this absorbing material, the CoFe2O4 particle size is relatively small, and the stacked folds with RGO form a "sandwich" structure containing many irregular pores / channels, which greatly enhances the magnetic permeability and magnetic concentration effect of the composite magnetic material in a specific frequency band, and reduces the magnetic loss of the composite magnetic material in a specific frequency band. The two components work together to achieve the best impedance matching and excellent attenuation characteristics, which is more in line with the current requirements of new electromagnetic wave absorbing materials to be "thin", "light", "wide" and "strong". BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the transmission electron microscope image of CoFe2O4 / RGO prepared in Example 3.

[0028] Figure 2 This is the X-ray diffraction pattern of CoFe2O4 / RGO prepared in Example 3.

[0029] Figure 3 This is a graph showing the relationship between (a) real part of dielectric, (b) imaginary part of dielectric, (c) real part of magnetic permeability, (d) imaginary part of magnetic permeability, (e) dielectric loss coefficient and (f) magnetic loss coefficient and frequency for CoFe2O4 / RGO prepared in Example 3 in the range of 2 to 18 GHz.

[0030] Figure 4 (a) Reflection loss 3D graph and (b) reflection loss 2D graph of CoFe2O4 / RGO prepared in Example 3.

[0031] Figure 5 This is a frequency-dependent reflection loss curve of CoFe2O4 / RGO prepared in Example 3 at different thicknesses.

[0032] Figure 6 This is a graph showing the relationship between (a) attenuation constant and (b) impedance matching coefficient and frequency for CoFe2O4 / RGO prepared in Example 3 in the range of 2 to 18 GHz. DETAILED DESCRIPTION

[0033] In the following embodiments, the RGO solutions were prepared by the following preparation method: 140 mg of graphite oxide powder and 140 mg of sodium dodecylbenzene sulfonate were dispersed in 140 mL of deionized water by a redox method, 0.5 mL of 80 wt % hydrazine hydrate was added, and the mixture was reacted in a water bath at 80 ° C for 24 h to obtain RGO. After the reaction, the RGO was collected and washed by filtration, and finally dispersed in ethylene glycol to obtain an RGO solution with a concentration of 0.7 mg / mL.

[0034] Example 1

[0035] 10 mL of ethylene glycol solution containing RGO was transferred, 0.68 g of FeCl3·6H2O and 0.6 g of CoCl2·6H2O were added thereto, 50 mL of ethylene glycol was added after ultrasonic dispersion and mixing, followed by 0.9 g of sodium acetate and 0.2 g of polyethylene glycol, and the mixture was transferred into a round-bottom flask after continued ultrasonic dissolution. After stirring at 25 °C for 1 h, the mixture was transferred into a 100 mL polytetrafluoroethylene reactor and reacted at 120 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic separation, washed with deionized water and anhydrous ethanol for 3 times, and dried to obtain the CoFe2O4 / RGO composite material.

[0036] Example 2

[0037] 30 mL of ethylene glycol solution containing RGO was transferred, 2.70 g of FeCl3·6H2O and 0.6 g of CoCl2·6H2O were added thereto, 30 mL of ethylene glycol was added after ultrasonic dispersion and mixing, followed by 1.8 g of sodium acetate and 0.5 g of polyethylene glycol, and the solution was transferred into a round-bottom flask after continued ultrasonic dissolution. After stirring at 40 °C for 2 h, the solution was transferred into a 100 mL polytetrafluoroethylene reactor and reacted at 140 °C for 6 h. After cooling to room temperature, the solution was separated by magnetic separation, washed with deionized water and anhydrous ethanol for 3 times, and dried to obtain the CoFe2O4 / RGO composite material.

[0038] Example 3

[0039] 30 mL of ethylene glycol solution containing RGO was transferred, 1.35 g of FeCl3·6H2O and 0.6 g of CoCl2·6H2O were added thereto, 30 mL of ethylene glycol was added after ultrasonic dispersion and mixing, followed by 1.8 g of sodium acetate and 0.5 g of polyethylene glycol, and the solution was transferred into a round-bottom flask after continued ultrasonic dissolution. After stirring at 50 °C for 1 h, the solution was transferred into a 100 mL polytetrafluoroethylene reactor and reacted at 200 °C for 8 h. After cooling to room temperature, the solution was separated by magnetic separation, washed with deionized water and anhydrous ethanol for 3 times, and dried to obtain the CoFe2O4 / RGO composite material.

[0040] Example 4

[0041] 40 mL of ethylene glycol solution containing RGO was transferred, 1.35 g of FeCl3·6H2O and 1.19 g of CoCl2·6H2O were added thereto, 20 mL of ethylene glycol was added after ultrasonic dispersion and mixing, followed by 1.8 g of sodium acetate and 1.0 g of polyethylene glycol, and the solution was transferred into a round-bottom flask after continued ultrasonic dissolution. After stirring at 60 °C for 3 h, the solution was transferred into a 100 mL polytetrafluoroethylene reactor and reacted at 180 °C for 8 h. After cooling to room temperature, the solution was separated by magnetic separation, washed with deionized water and anhydrous ethanol for 3 times, and dried to obtain the CoFe2O4 / RGO composite material.

[0042] Example 5

[0043] 50 mL of ethylene glycol solution containing RGO was transferred, 2.70 g of FeCl3·6H2O and 1.19 g of CoCl2·6H2O were added thereto, 10 mL of ethylene glycol was added after ultrasonic dispersion and mixing, followed by 1.8 g of sodium acetate and 0.5 g of polyethylene glycol, and the mixture was transferred into a round-bottom flask after continued ultrasonic dissolution. After stirring at 70 °C for 1 h, the mixture was transferred into a 100 mL polytetrafluoroethylene reactor and reacted at 200 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic separation, washed with deionized water and anhydrous ethanol for 3 times, and dried to obtain the CoFe2O4 / RGO composite material.

[0044] Example 6

[0045] 60 mL of ethylene glycol solution containing RGO was transferred, 5.40 g of FeCl3·6H2O and 1.19 g of CoCl2·6H2O were added thereto, 4.5 g of sodium acetate and 1.5 g of polyethylene glycol were added after ultrasonic dispersion and mixing, and the mixture was transferred into a round-bottom flask after continued ultrasonic dissolution. The mixture was stirred at 80 °C for 1 h and then transferred into a 100 mL polytetrafluoroethylene reactor. The mixture was reacted at 160 °C for 10 h and cooled to room temperature before magnetic separation. The mixture was washed with deionized water and anhydrous ethanol for 3 times and dried to obtain the CoFe2O4 / RGO composite material.

[0046] The CoFe2O4 / RGO prepared in Example 3 was characterized by transmission electron microscopy (TEM). Figure 1 As shown in the figure, the large area of ​​wrinkled material is RGO, and it can be clearly observed that the black nanoparticles with larger particle size are CoFe2O4 nanoparticles. The black nanoparticles are irregular spherical, with a smooth surface and a particle size of about 30nm, and are evenly loaded on the RGO surface.

[0047] The crystal form of CoFe2O4 / RGO prepared in Example 3 was analyzed by X-ray diffraction (XRD). Scanning range 20~70°. Figure 2It can be seen that by comparing with the standard card (JCPDS22-1086), it is found that the diffraction peaks of 2θ at 18.3°, 30.1°, 35.3°, 43.1°, 57.0° and 62.3° are consistent with the (111), (220), (311), (400), (511) and (440) crystal planes of CoFe2O4. The absence of the characteristic diffraction peak of RGO is due to the strong diffraction of CoFe2O4, indicating that a pure phase CoFe2O4 / RGO composite material was prepared.

[0048] Study on microwave absorption performance

[0049] The CoFe2O4 / RGO electromagnetic wave absorbing material prepared in the above Example 3 is subjected to a wave absorbing performance test, comprising the following steps:

[0050] (1) Testing electromagnetic parameters: The obtained product was ground and mixed with paraffin wax at a mass ratio of 3:2, and pressed into a coaxial ring with an outer diameter of 7 mm, an inner diameter of 3 mm, and a thickness of 3 mm in a special mold. The electromagnetic parameters, real part of magnetic permeability μ′, imaginary part of magnetic permeability μ″, real part of dielectric ε′, and imaginary part of dielectric ε″ were tested in the range of 2 to 18 GHz using a vector network analyzer;

[0051] (2) Calculate the reflection loss value of the sample: According to the transmission line theory formula:

[0052]

[0053] Calculate the theoretically achieved reflection loss value, and the value obtained from the theoretical calculation reflects the attenuation coefficient and impedance matching performance of the absorbing material;

[0054] (3) Plot the frequency relationship of the complex dielectric constant and magnetic permeability of the sample in the frequency range of 2 to 18 GHz, as well as the reflection loss diagram. Based on theoretical calculations, the reflection loss values ​​of the sample at different thicknesses are intuitively compared to the high-performance electromagnetic wave absorption value at ultra-thin thickness.

[0055] Depend on Figure 3 It can be seen that in the frequency range of 2 to 18 GHz, the ε′ and ε″ of the CoFe2O4 / RGO composite material are between 7.52 and 12.65 and 3.85 to 5.96, respectively, and the μ′ and μ″ of the CoFe2O4 / RGO composite material are between 0.88 and 1.02 and -0.16 to 0.10, respectively; it is also found that with the addition of RGO, the ε′ and ε″ values ​​are greatly increased. This phenomenon shows that the introduction of RGO can greatly improve the dielectric constant of the CoFe2O4 / RGO composite material, which is due to the high conductivity of RGO and the synergistic effect of the CoFe2O4 / RGO composite material. In addition, the relaxation and polarization of residual defects and RGO surface groups can enhance the dielectric constant in the electromagnetic wave range.

[0056] The imaginary part μ″ value of the magnetic permeability of CoFe2O4 nanoparticles is higher than that of the CoFe2O4 / RGO composite material in the entire test range, which means that CoFe2O4 nanoparticles have a stronger loss capacity for magnetic energy, which is related to the fact that the introduced RGO is a non-magnetic material. In addition, it was found that the imaginary part of the magnetic permeability (μ″) of the sample showed multiple resonance peaks in the frequency range of 2 to 18 GHz, which was caused by exchange resonance. It was also noted that the imaginary part of the magnetic permeability (μ″) of the sample showed negative values ​​in the frequency range of 10 to 18 GHz, which was attributed to the fact that the magnetic energy of the electromagnetic wave was scattered and not absorbed by the material.

[0057] It can be seen from the relationship between the loss coefficient and the frequency that the dielectric loss coefficient (tanδ ε ) and magnetic loss coefficient (tanδ μ ) values ​​show some fluctuations in the measured frequency range, and the addition of RGO clearly observed an increase in tanδ ε The value is enhanced because RGO can change the conductivity of CoFe2O4 and provide conditions for interface polarization. The improvement of material conductivity and polarization effect will increase its dielectric loss. ε The value shows an upward trend with the increase of frequency, while the tanδ μ The value shows a downward trend, tanδ ε The value is significantly greater than tanδ μ This indicates that the electromagnetic wave loss of CoFe2O4 / RGO composite is dominated by dielectric loss.

[0058] However, the electromagnetic wave absorption characteristics of the material are determined by its dielectric loss and magnetic loss. Pure dielectric loss or magnetic loss cannot achieve excellent electromagnetic wave absorption effect. The magnetic loss of the sample mainly comes from natural resonance loss and eddy current loss. Figure 4 and Figure 5 It can be seen that the CoFe2O4 / RGO electromagnetic wave absorption material has a thickness of 2.3mm, a minimum RL of -59.2dB, and an absorption bandwidth of less than 10dB in the range of 2 to 18GHz at a frequency of 11.32GHz, reaching 9.52GH.

[0059] Excellent electromagnetic wave absorbing materials are required not only to have strong absorption capacity, but also to have a wide absorption band, which requires that the electromagnetic waves can enter the material to the maximum extent (impedance matching characteristics) and the electromagnetic waves entering the material can be lost to the maximum extent (attenuation characteristics). Figure 6It can be seen that in the range of 2 to 18 GHz, the attenuation coefficient of the sample increases monotonically. It can also be clearly seen from the figure that the addition of RGO greatly increases the attenuation coefficient of the material, indicating that reduced graphene oxide can effectively improve the material's ability to attenuate electromagnetic waves. High-quality electromagnetic wave absorption materials not only require strong electromagnetic wave attenuation capabilities, but also need to have better impedance matching characteristics. When the electromagnetic wave loss is optimal, the impedance matching coefficient (Z) value is close to 1, indicating good impedance matching performance, then more electromagnetic waves will effectively enter the electromagnetic wave absorption material, and effectively converted into heat energy or dissipated at the interface, achieving high-performance electromagnetic wave absorption at multiple thicknesses including thinner thicknesses, and is expected to become an ideal lightweight electromagnetic wave absorption material.

[0060] Comparative Example 1

[0061] 1.35gFeCl3·6H2O and 0.6gCoCl2·6H2O were added to 60mL of ethylene glycol, and 1.8g sodium acetate and 0.5g polyethylene glycol were added and ultrasonically dispersed and mixed evenly. The mixture was then transferred to a round-bottom flask and stirred at 50°C for 1h. The mixture was transferred into a 100mL polytetrafluoroethylene reactor and reacted at 200°C for 8h. The mixture was cooled to room temperature and separated by magnetic separation. The mixture was washed with deionized water and anhydrous ethanol for 3 times and dried to obtain CoFe2O4 nanoparticles.

[0062] Comparative Example 2

[0063] 1.35g FeCl3·6H2O, 0.6g CoCl2·6H2O and 2mg graphite oxide powder (GO) were ultrasonically dispersed in 60mL ethylene glycol, followed by adding 1.8g sodium acetate and 0.5g polyethylene glycol. After continued ultrasonic dissolution, the mixture was transferred to a round-bottom flask, stirred at 50°C for 1h, and then transferred into a 100mL polytetrafluoroethylene reactor. The mixture was reacted at 200°C for 8h, cooled to room temperature, and then magnetically separated. The mixture was washed three times with deionized water and anhydrous ethanol and dried to obtain a CoFe2O4RGO composite material.

[0064] The materials obtained in Example 6 and Comparative Examples 1 and 2 were tested for their absorbing performance according to the same absorbing performance test method in the study of absorbing performance, and the results are shown in Table 1. The thickness refers to the material thickness corresponding to the minimum reflection loss value.

[0065] Table 1 Comparison of sample absorption performance parameters

[0066]

[0067] As shown in Table 1, since it is only a single magnetic medium type material, the CoFe2O4 obtained in Comparative Example 1 exhibits the disadvantages of strong attenuation ability, poor impedance matching, high density, aggregation and large coating thickness, and cannot meet the requirements of broadband and lightweight. The minimum reflection loss of the CoFe2O4 / GO material obtained in Comparative Example 2 is weak, the effective bandwidth is narrow, and it cannot effectively absorb electromagnetic waves at a thinner thickness. The composite material obtained in Example 6 can absorb electromagnetic waves at a thinner thickness, but the impedance matching ability is poor, and the ability of electromagnetic waves to enter the interior of the material is poor. The composite material obtained in Example 3 has a strong minimum reflection loss, a wide effective bandwidth, and excellent electromagnetic wave absorption effect at a thinner thickness.

[0068] Table 2 Comparison of material properties with those reported in the literature

[0069]

[0070]

[0071] Table 2 is a comparison of the properties of the composite material obtained in Example 3 and the materials reported in the literature. As shown in Table 2, the material components in these reports are the same as those in the present invention, but the methods used are not as simple, fast, low-carbon and environmentally friendly as the methods in the present invention.

[0072] In addition, the best absorbing effects reflected by the absorbing parameters are not as good as the absorbing performance of the CoFe2O4 / RGO nanocomposite material prepared in Example 3. The reason is that the CoFe2O4 / RGO nanocomposite material prepared in Example 3 has a smaller CoFe2O4 particle size (is there any particle size data in the example), and the stacked folds of RGO form a "sandwich" structure containing many irregular pores / channels, which greatly enhances the magnetic permeability and magnetic concentration effect of the composite magnetic material in a specific frequency band, and reduces the magnetic loss of the composite magnetic material in a specific frequency band. The two components work together to achieve the best impedance matching and excellent attenuation characteristics, which is more in line with the current requirements of "thin, light, wide and strong" for new electromagnetic wave absorption materials.

[0073] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a graphene magnetic absorbing material, characterized in that: The iron source and the cobalt source are dispersed in the RGO solution, and then sodium acetate and polyethylene glycol are dissolved therein, and the mixture is heated for reaction and then cooled, and then separated, washed and dried to obtain the CoFe2O4 / RGO composite material; The molar ratio of iron to cobalt in the iron source and the cobalt source is (1-4):1; The mass ratio of the iron source, the cobalt source and the RGO in the RGO solution is (53-81):(17.7-46.7):(0.3-1.3); The mass ratio of RGO, sodium acetate and polyethylene glycol is (0.007-0.042):(1.8-4.5):(0.2-1.5).

2. The method for preparing the graphene magnetic absorbing material according to claim 1, characterized in that: The iron source is FeCl3·6H2O; The cobalt source is CoCl2·6H2O.

3. The method for preparing the graphene magnetic absorbing material according to claim 1, characterized in that: The preparation method of the RGO solution comprises the following steps: dispersing graphite oxide powder and sodium dodecylbenzene sulfonate in water and adding hydrazine hydrate solution, filtering and washing after water bath reaction to obtain RGO; and then dispersing the RGO in ethylene glycol to obtain the RGO solution.

4. The method for preparing the graphene magnetic absorbing material according to claim 1, characterized in that: The conditions for incorporating sodium acetate and polyethylene glycol are as follows: adding sodium acetate and polyethylene glycol to the RGO solution, ultrasonically treating the solution, and stirring the solution at 25-80° C. for 1-5 h before heating the solution for reaction.

5. The method for preparing the graphene magnetic absorbing material according to claim 1, characterized in that: The heating reaction conditions are: 120-200°C for 6-10h.

6. The method for preparing the graphene magnetic absorbing material according to claim 3, characterized in that: The ratio of graphite oxide powder, sodium dodecylbenzene sulfonate and hydrazine hydrate solution is (120-150) mg: (110-150) mg: (0.3-1) mL, and the concentration of hydrazine hydrate solution is 70-85 wt%.

7. The method for preparing the graphene magnetic absorbing material according to claim 3, characterized in that: The conditions for the water bath reaction are: 70-90°C, 15-30h.

8. The method for preparing the graphene magnetic absorbing material according to claim 3, characterized in that: The concentration of RGO in the RGO solution is 0.5-1 mg / mL.

9. A graphene magnetic wave absorbing material, characterized in that: The absorbing material is prepared by the method described in any one of claims 1 to 8; and in the absorbing material, CoFe2O4 nanoparticles are loaded on the RGO with laminated wrinkles to form a sandwich structure containing irregular pores and / or channels; Wherein, the particle size of CoFe2O4 nanoparticles is 10-40nm.

10. Application of the graphene magnetic wave absorbing material prepared by the method according to any one of claims 1 to 8 in electromagnetic wave absorption.

Citation Information

Patent Citations

  • Method for preparing reduced graphene oxide / CoFe2O4 / Ag composite wave-absorbing material

    CN104673185A

  • Preparation method for reduced graphene oxide / Ni-Co ternary composite wave-absorbing material

    CN105295832A

  • RGO / CoFe2O4 / Y3Fe5O12 composite powder and preparation method thereof

    CN105670558A

  • Preparation method of reduced graphene oxide / manganese ferrite nano-composite wave absorbing material

    CN108559445A

  • Graphene / metal oxide / metal ternary nano composite magnetic material and preparation method thereof

    CN111613901A

Cited By

  • Lightweight flexible wave-absorbing / heat-conducting bifunctional film material and preparation method thereof

    CN120625261A

  • Lotus leaf carbon-based iron-cobalt composite hollow broadband wave-absorbing material as well as preparation method and application thereof

    CN120790928A

  • Egg yolk shell structure (magnetic metal-carbon)-air-porous carbon composite wave-absorbing material and preparation method thereof

    CN121152196A

  • Ternary heterostructure CoFe2O4 / ZnO-RGO nano composite electromagnetic wave absorbing material as well as preparation method and application thereof

    CN121376994A